2013
DOI: 10.1186/1471-2156-14-59
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cytogenetic analysis of some species of the Dendropsophus microcephalus group (Anura, Hylidae) in the light of phylogenetic inferences

Abstract: BackgroundDendropsophus is a monophyletic anuran genus with a diploid number of 30 chromosomes as an important synapomorphy. However, the internal phylogenetic relationships of this genus are poorly understood. Interestingly, an intriguing interspecific variation in the telocentric chromosome number has been useful in species identification. To address certain uncertainties related to one of the species groups of Dendropsophus, the D. microcephalus group, we carried out a cytogenetic analysis combined with phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(71 citation statements)
references
References 28 publications
2
50
0
19
Order By: Relevance
“…Samples of genomic DNA were obtained from Dendropsophus seniculus (ZUEC 17225), D. soaresi (ZUEC 16867) and D. novaisi (ZUEC 17858) following the procedure reported by Medeiros et al (2013). A fragment of approximately 1300 bp of the 16S ribosomal RNA gene was PCR-amplified using the primers 12L13(L) (Feller and Hedges 1998) and 16Sbr(H) (Palumbi et al 1991).…”
Section: Mitochondrial Dna Sequencesmentioning
confidence: 99%
See 4 more Smart Citations
“…Samples of genomic DNA were obtained from Dendropsophus seniculus (ZUEC 17225), D. soaresi (ZUEC 16867) and D. novaisi (ZUEC 17858) following the procedure reported by Medeiros et al (2013). A fragment of approximately 1300 bp of the 16S ribosomal RNA gene was PCR-amplified using the primers 12L13(L) (Feller and Hedges 1998) and 16Sbr(H) (Palumbi et al 1991).…”
Section: Mitochondrial Dna Sequencesmentioning
confidence: 99%
“…Although all of the Dendropsophus species karyotyped to date show 2n = 30 (see review in Catroli and Kasahara 2009, Medeiros et al 2013, Suárez et al 2013, Oliveira et al 2016), a noticeable variation in the number of biarmed/telocentric chromosomes is observed among them, suggesting that several chromosomal rearrangements took place after the evolutionary origin of the hypothetical ancestral 30-chromosome karyotype. Karyotypes with only biarmed chromosomes [as in D. minutus (Peters, 1872) (Gruber et al 2005) and D. leali (Bokermann, 1964) (Bogart 1973)] and karyotypes with up to five pairs of telocentric/subtelocentric chromosomes [as in D. labialis (Peters, 1863) (Bogart 1973), D. sanborni (Schmidt, 1944) and D. jimi (Napoli & Caramaschi, 1999) (Medeiros et al 2013)] may be observed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations